AquaNet - Automatic sensors from Feresjön AquaNet platform - Asa Research Station (Swedish University of Agricultural Sciences, 2024)
Automatic sensor data from the AquaNet mesocosm facility.
Asa Research Station (2024). AquaNet - Automatic sensors from Feresjön AquaNet platform, 2018-07-20–2018-08-16 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/t97iY9FvIc6OQbfTo_x7qYio
Keywords: SITES AquaNet; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap